(untitled) (Interdisciplinary Studies Journal, 2024)
In Brazil, the prevalence of pregnant teenagers is a public health problem requiring effective actions. The research aimed to evaluate the temporal trend and factors associated with early pregnancy in the municipality of Vitória do Xingu, Pará. Data from 3,143 pregnant women were obtained from the Information System on Live Births (SINASC), between 2011 and 2020. Maternal, gestational, and newborn characteristics were analyzed. Fertility and growth rates and the Odds ratio were calculated. Additionally, the Annual Increment Rate (TIA) was calculated from the regression data. The study indicated an increase in the prevalence of pregnant adolescents in the municipality investigated due to the lack of effective public policies for this public and is related to the situation of socioeconomic vulnerability in which the adolescent is inserted. The present study helps health professionals to implement strategies aimed at promoting the health of adolescents, especially those in vulnerable conditions.